Caracterização e utilização do resíduo de cerâmica vermelha como material pozolânico em matrizes cimentantes - Cassol, Gabriela [UNESP] (2015)
Recent researches has shown that Red Ceramic Waste (RCW) has characteristics that may be interesting in the production of cementitious materials. The objective, of this study is to evaluate the pozzolanic activity of the red ceramic waste finely ground in the production of Portland cement. Were performed initial testing to determine the optimal time for grinding of the RCW. Then, there was the chemical and physical characterization of the waste, by tests of microanalysis, X-ray diffractometry, thermogravimetric analysis, loss on fire and scanning electron microscopy. Finally, were carried out for compressive strength tests in different compositions of mortar, varying the substitution waste content of the Portland cement. Through these tests, one can said that the RCW has pozzolanic activity, because it has in its chemical composition of silica and alumina, and even presenting big part of its elements in crystalline state, was observed by thermogravimetric analysis that the RCW consumes calcium hydroxide confirming its pozzolanic activity, making future can be introduced in the composition of blended cements